Konsep Umum dan Fungsi Desain Pembelajaran Pendidikan Agama Islam (PAI) - Asep Hidayat; Shalahuddin Shalahuddin; Ade Irawan; Rika Rahmanita; Melvi Melinda (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Learning design is a fundamental component in the educational process, as it serves as a foundation for teachers in planning, implementing, and evaluating learning activities systematically and purposefully. In the context of Islamic Religious Education (PAI), learning design has a broader role, not only focusing on the delivery of religious knowledge, but also encompassing the formation of character, morals, and strengthening Islamic values ​​in students. This paper discusses the general concept and function of learning design in PAI through theoretical studies from various literature and expert views. The results of the discussion indicate that PAI learning design must be prepared comprehensively by considering the components of objectives, materials, methods, media, and evaluation that are aligned with Islamic values. In addition, learning design serves as a practical guideline for teachers to create effective, efficient, innovative learning that is able to respond to the challenges of modern developments. Good learning design also contributes to increased learning motivation, optimal achievement of competencies, and the formation of students who are faithful, pious, and have good morals. Thus, understanding the concept and function of learning design is crucial for educators in their efforts to improve the quality of PAI learning as a whole.